NEEDS ANALYSIS OF ENGLISH LITERATURE STUDENTS IN ENGLISH ORAL COMMUNICATION - Angga Maulana; Fegy Lestari (Eltin Journal : Journal of English Language Teaching in Indonesia, 2017)
The purpose of this study is to identify factual information about the needs of students of English Literature in the activities and supporting factors of oral communication by using English, whether linguistic and non-linguistic, and analyzing the difficulties of the situation of oral communication of English Literature students using English. This research uses descriptive method. Data collection is done through two stages: the questionnaire and the interview, followed by the review of someliteratures. The results of this study indicate that in general the students of English Literature feel that participating in a formal discussion is more important than the informal. While in terms of ability in the oral communication activity, generally students mastered informal communication activities. In terms of linguistic factors, the choice of vocabularies, and good and correct sentences are considered very important, although they only feel quite capable in it. It is also found that talking with self-confidence, having proper English pronunciation and mastering the topic of conversation become the important non-linguistic factors. The same thing does not happen on loudness and facial mimic. In general, students feel it is not important enough to master. Regarding situations that facilitate students in oral communication in English, they generally feel that well preparation, self-confidence, and mastery over vocabulary and what is being discussed becomes an easier factor. Different things revealed by most students about the difficult vocabulary and the lack of preparation in oral communication. It is difficult. As for things that require improvement, students generally feel that the confidence and the amount of vocabulary that is mastered should be improved in order to improve the quality of oral communication in English.